World Heritage List: Does It Make Sense? - Bruno S. Frey; Lasse Steiner (Center for Research in Economics, Management and the Arts (CREMA), 2010)
The UNESCO World Heritage List contains the 900 most treasured Sites of humanity's culture and landscapes. The World Heritage List is beneficial where heritage sites are undetected, disregarded by national decision-makers, not commercially exploitable, and where national financial resources, political control and technical knowledge for conservation are inadequate. Alternatives such as the market and reliance on national conservation list are more beneficial where the cultural and natural sites are already popular, markets work well, and where inclusion in the List does not raise the destruction potential by excessive tourism, and in times of war or by terrorists.
Keywords: Z11; D6; F5; H87; 330; Global public good; World Heritage; Cultural Certificates; Monuments; UNESCO